2013
DOI: 10.1007/s10339-013-0551-7
|View full text |Cite
|
Sign up to set email alerts
|

Finding faults: analogical comparison supports spatial concept learning in geoscience

Abstract: A central issue in education is how to support the spatial thinking involved in learning science, technology, engineering, and mathematics (STEM). We investigated whether and how the cognitive process of analogical comparison supports learning of a basic spatial concept in geoscience, fault. Because of the high variability in the appearance of faults, it may be difficult for students to learn the category-relevant spatial structure. There is abundant evidence that comparing analogous examples can help students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 47 publications
4
43
0
1
Order By: Relevance
“…Further, we predicted that verbal analogical reasoning would be more important in science than maths, and this was supported by the behavioral analyses: correlations with science were higher, and the correlation with maths disappeared when verbal IQ and VSWM were controlled for. These results are in line with the suggestion that science learning requires verbal encoding of associations (Tolmie et al, ) and is supported by analogical reasoning (Jee et al, ; Matlen et al, ; Vendetti et al, ). Although participants recruited the RLPFC, DLPFC, VLPFC, and parietal cortex regions previously implicated in relational reasoning when resolving science problems, we did not observe the predicted correlation between activation in these regions and individual differences in verbal analogical reasoning scores.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Further, we predicted that verbal analogical reasoning would be more important in science than maths, and this was supported by the behavioral analyses: correlations with science were higher, and the correlation with maths disappeared when verbal IQ and VSWM were controlled for. These results are in line with the suggestion that science learning requires verbal encoding of associations (Tolmie et al, ) and is supported by analogical reasoning (Jee et al, ; Matlen et al, ; Vendetti et al, ). Although participants recruited the RLPFC, DLPFC, VLPFC, and parietal cortex regions previously implicated in relational reasoning when resolving science problems, we did not observe the predicted correlation between activation in these regions and individual differences in verbal analogical reasoning scores.…”
Section: Discussionsupporting
confidence: 90%
“…A third study revealed that a combined measure of relational reasoning, which included numerical reasoning, verbal analogical reasoning, and spatial reasoning, predicted maths learning in 11‐ to 14‐year olds over 2 years (Primi, Ferrão, & Almeida, ). Other studies have shown teaching by analogy to improve maths performance in adults (Richland & McDonough, ), and science performance in 9‐ to 10‐year olds (Matlen, Vosniadou, Jee, & Ptouchkina, ) and adults (Jee et al, ).…”
mentioning
confidence: 95%
“…We know from many laboratory studies that analogical mapping can promote learning in science, mathematics, and engineering (Bassok & Holyoak, 1989;Goldstone & Son, 2005;Jee et al, 2013;Reed, Dempster, & Ettinger, 1985;Ross & Kilbane, 1997;Schwartz, Chase, Oppezzo, & Chin, 2011;Vosniadou, 1989). Analogical processing is a powerful learning mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…They also learn about the causal processes that create these structures-both local deformation processes that create faults and folds, and large-scale global processes such as tectonic movements. All these topics are intensely spatial Jee et al 2013;Kastens et al 2009;Libarkin and Brick 2002). Consider, for example, the geologic concept of a fault-a fracture in rock along which movement has occurred ( Fig.…”
Section: Spatial and Causal Knowledge In Geosciencementioning
confidence: 99%